Guide for Small Community Water Suppliers and Local Health Officials on Lead in Drinking Water - Hayes, Colin (IWA Publishing, 2010)
"This Guide for Small Community Water Suppliers and Local Health Officials is one of a series produced by the International Water Association's (IWA) Specialist Group on Metals and Related Substances in Drinking Water. It is an abbreviated compilation of the wide range of scientific, engineering, health and operational issues concerned with the control of lead in drinking water in small water supply systems. The IWA Specialist Group is supported by members from 26 European countries, Canada and the United States. It is an active research network and has regularly convened international conferences and seminars. It has close working links with the World Health Organization, the European Commission's Joint Research Centre, Health Canada and the US Environmental Protection Agency. The IWA Specialist Group developed out of COST Action 637 (www.cost.esf.org), a European research network. The Guide is supported by a two-day technical training course and a more comprehensive Best Practice Guide on the Control of Lead in Drinking Water (IWA, 2010). Information about training, the Best Practice Guide and the research network in general is available from www.meteau.org This Guide for Small Community Water Suppliers and Local Health Officials explains why lead in drinking water may still be a threat to public health in small communities. It is aimed at Local Health Officials and the operators of drinking water supply systems that serve small communities. Its objectives are to raise awareness, to provide a basis for assessing the extent of problems, and to identify control options. "